Hostis Honori Invidia – Hate Makes the Opponent Honor Xenophobia and Reconciliation. An Exemplary Analysis of the Relation between Germans and Poles - Sadziński, Witold (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
The article refutes the thesis put forward by Kurt Lück (Der Mythos vom Deutschen in der polnischen Volksüberlieferung und Literatur [The Myth of the Germans in Polish Folk Tradition and Literature], 1943) that peace-loving Germans have been unjustly hated by Poland since ancient times, while the opposite is not true. The reason for this may be the cognitively differently interpretable linguistic images, that are triggered by hassen resp. nienawidzić [to hate]. The main emphasis, however, is placed on the process of reconciliation between Germans and Poles. The conclusion is that xenophobia usually results from a lack of communication. Enemies do not talk to each other - they fight or hate each other. Hatred is thus a symptom of weakness and does honor to the opponent, as the Romans already knew: hostis honori invidia. It turns out that only the mutual willingness to dismantle mutual prejudices and to conduct proper discussions slowly leads to a gradual rapprochement: “German historians no longer invoke the urge to the east as a civilizing mission of their people. Their Polish colleagues have stopped demonizing the Knights of the Order and portraying this Order as another link in the allegedly consistent and centuries-old urge of Germans to move to the East“ (Tazbir 1993: 34).